2012
DOI: 10.1021/jz301911y
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Properties of Carbon Dots Revealed After HPLC Fractionation

Abstract: Carbon dots (C-dots) are often synthesized, modified, and studied as a mixture. Unfortunately, the spectroscopic and biological properties measured for such C-dots assume that there is a high degree of homogeneity in the produced sample. By means of high-resolution separation techniques, we show that "as-synthesized" C-dots exist as a relatively complex mixture and that an unprecedented reduction in such complexity can reveal fractions of C-dots with unique luminescence properties. The wavelength-dependent pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
98
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 43 publications
3
98
0
Order By: Relevance
“…Using the nitric acid-sulfuric acid mixture, we found that, after 1 h of reaction, luminescent nanoparticle fractions were regenerated that had chromatographic patterns and elution times similar to those obtained from GNFs. 4 To investigate whether, indeed, different bulk carbon starting materials could be used to reproduce similar C-dots species, the oxidation of CFs was followed for seven days using AE-HPLC (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the nitric acid-sulfuric acid mixture, we found that, after 1 h of reaction, luminescent nanoparticle fractions were regenerated that had chromatographic patterns and elution times similar to those obtained from GNFs. 4 To investigate whether, indeed, different bulk carbon starting materials could be used to reproduce similar C-dots species, the oxidation of CFs was followed for seven days using AE-HPLC (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…9 Carbon dots have also been synthesized from CFs by electrochemical etching; 22 other reports of CF-derived CNPs use single-temperature and reaction-time conditions. 10 Although there is a plethora of literature on various reaction conditions at different temperatures and oxidizing conditions using nitric acid only, 3 nitric acidsulfuric acid mixtures, 4 and modified Hummers' methods, 5 there is a distinct lack of fundamental studies and understanding of the reaction dynamics and the species produced at various time points. Furthermore, a detailed study of intact CFs treated under a mixture of nitric and sulfuric acids has previously revealed that oxygen-, nitrogen-, and sulfur-containing groups varied discontinuously over time on the CF surface, especially in the early stages of reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the intensive research efforts carried out in the past decades, the scientific community nowadays understands much better the structural, photophysical, and chemical properties of C-dots; however, the complete characterization of C-dots mixture still remains unachieved and faces noteworthy challenge. This is due to the fact that a C-dots product exists as a complex mixture comprising components with various sizes and different surface functionalities, and a polydisperse C-dots sample only represents the summation or average properties of all individual C-dots species [95,100,101]. In this sense, there is an urgent need for the development of efficient analytical separation methods to isolate high-purity C-dots fractions for more precious investigation of their unique chemical and photophysical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the semiconductor quantum dots derived from heavy metal precursors incurring long term toxicity [11], C-dots are environmentally friendly and lack of known cytotoxicity [12,13]. The spectroscopic studies have shown that the mixture of C-dots of different sizes with the ability to emit in different color at different excitation wavelength [14]. The multicolor property of C-dots has made them promising "nano-lights" that can emit tuneable photoluminescence for various applications.…”
Section: Introductionmentioning
confidence: 99%